Growth, hemato-biochemical, immune-antioxidant response, and gene expression in Nile tilapia (Oreochromis niloticus) received nano iron oxide-incorporated diets. Issue 128 (September 2022) - Elabd, Hiam; Youssuf, Hadeer; Mahboub, Heba H.; Salem, Shimaa M.R.; Husseiny, Walaa A.; Khalid, A.; El-Desouky, Heba S.; Faggio, Caterina
Abstract: Nanotechnology has recently played a key role in tackling many aquacultures issues. Hence, the present study targets the evaluation of dietary inclusion of nano iron oxide (nFe2 O3 ) on growth performance, hematology, immune-antioxidant responses, ionic regulation and expression of related genes in Nile tilapia ( Oreochromis niloticus ). Fish were fed supplementary nFe2 O3 at rates of zero (control), 0.5, and 1 g/kg diet for 30 days. Obtained data demonstrated that nFe2 O3 significantly ( P < 0.05) augmented growth performance (final weight and length, body mass gain, specific growth rate, feed conversion ratio, and length gain rate). Hematological picture {RBCs, Hb, MCV, MCH and MCHC, and leukocytes interpretations (WBCs and monocytes)}; and biochemical indexes including (AST and ALT; total protein; and glucose, and cortisol) were significantly ( P < 0.05) improved in nFe2 O3 supplemented groups. Plasma ionic concentration was also altered with nFe2 O3 supplementation, and 1g nFe2 O3 revealed the most marked increase in plasma (Na + ) potassium (K + ) levels. Similarly, IgM, nitrous oxide (NO), and lysozyme activity, plus superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities showed a remarkable improvement in 1g nFe2 O3 group compared to the control. Expression of Insulin-Like Growth Factor-1 ( IGF-1 ) and interleukin 1- β ( IL-1β ) genes were significantly up-regulated in nFe2 O3 supplemented groups. Briefly, dietary nFe2 O3 inclusion had enhanced properties on growth; hemato-biochemical; immune, antioxidative profiles; and related genes expression of O. niloticus, with a recommended concentration of 1g nFe2 O3 . Graphical abstract: Schematic flowchart showing the experimental design of the incorporation of Nile tilapia diets with nano iron oxide (nFe2 O3 ) on different assayed indices. Image 1 Highlights: Nano iron oxide (nFe2 O3 ) improves growth parameters and hematology in Nile tilapia. The immune-antioxidant responses are enhanced by 1 g nFe2 O3 dietary inclusion. Dietary incorporation with 1 g nFe2 O3 regulates ionic exchange. One gram of nFe2 O3 modulates liver functions, total protein, and stress indicators. Supplemented diet with 1 g nFe2 O3 up-regulates IGF-1 and 1-β ( IL-1β ) genes.